Correlation between the Alvarado Scale and the macroscopic aspect of the appendix in patients with appendicitis - Sousa-Rodrigues,Célio Fernando de (2014)
Objective: To evaluate the possible association between the scale of Alvarado (EA) and macroscopic appearance (MA) of the appendix in patients with acute appendicitis.Methods: after receiving the diagnosis of acute appendicitis, EA data were collected. During appendectomy, MA data were collected. Data from patients without appendicitis were excluded. The Spearman correlation test was used to compare EA with Appendix MA (p < 0.05). Other variables were represented by simple frequency. The confidence interval (CI) of 95% was calculated for the correlation test.Results: Data were collected from 67 consecutive patients. The mean age was 37.1 ± 12.5 years and 77.6% of patients were male. The Spearman correlation test used for EA and MA was + 0.77 (95% CI 0.65-0.85, p < 0.0001).Conclusion: although correlation was not perfect, our data indicate that a high score on the scale of Alvarado in patients with appendicitis is correlated with advanced stages of the inflammatory process of acute appendicitis.